2019
DOI: 10.3390/ma12193222
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Residual Amount of Sr and Morphology of Eutectic Si Phase in A356 Alloy

Abstract: This paper studied the relationship between the residual amount of Sr and the morphology of the eutectic Si phase in A356 obtained through different modification treatment processes; additionally, the cooling rates of molds were studied. The eutectic Si phase revealed a satisfactory modification effect at residual Sr amounts above 0.01 wt % in A356 alloys cast using an iron mould. Complete modification of the eutectic Si phase could be achieved at a Sr additive amount 0.03 wt % in an A356 melt. The addition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Eguskiza [25] had found that after 5 hours of holding A356 in liquid state had caused up to 40% of Sr loss from the matrix which had resulted in formation of SrO on the surface. A similar finding was reported by Zhang [26] where it was claimed that 150 minutes was good enough for A356 holding at 750 o C for the fading of Sr. According to SEM-EDS and XPS results, it can be seen that the surface oxide consists of Si and thereby SiO2 is formed.…”
Section: Resultssupporting
confidence: 87%
“…Eguskiza [25] had found that after 5 hours of holding A356 in liquid state had caused up to 40% of Sr loss from the matrix which had resulted in formation of SrO on the surface. A similar finding was reported by Zhang [26] where it was claimed that 150 minutes was good enough for A356 holding at 750 o C for the fading of Sr. According to SEM-EDS and XPS results, it can be seen that the surface oxide consists of Si and thereby SiO2 is formed.…”
Section: Resultssupporting
confidence: 87%
“…The previously determined loss rate constant (k) and surface reaction rate constant (k s ) offer a method for quickly estimating the fading of Na and Sr under production and/or experimental settings. The applicability of these constants for quantifying modifier fading is validated through literature data (Zhang et al 2019). Figure 7 presents experimental findings on the fading of Sr during its retention in a small laboratory furnace (with a surface area of approximately 0.015 m 2 ).…”
Section: Resultsmentioning
confidence: 87%
“…To the best of our knowledge, the relation of the presence of coarse eutectic silicon and π phase has been rarely reported in the literature. In the Sr-modified A356 alloy, Zhang et al [24] observed that the eutectic silicon near the π(Al 8 FeMg 3 Si 6 ) phases always exhibited incomplete modification. Nevertheless, some partially modified eutectic silicon was also observed in the sites without Fe at the edge of the eutectic structure in their research.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for the degradation of modification was attributed to the formation of (Mg 2 SrAl 4 Si 3 ) compounds. Zhang et al [24] suggested that the partially modified eutectic silicon was related to the formation of π(Al 8 FeMg 3 Si 6 ) phase in Sr-modified A356 alloy. Chacko et al [25] suggested that the modification efficiency of Sr deteriorated with the addition of Mg.…”
Section: Introductionmentioning
confidence: 99%